(untitled) (Revista de Ciências Agroveterinárias, 2024)
The aim of this study was to assess the in situ degradation of dry matter (DM), crude protein (CP), and neutral detergent fiber (NDF) in oat silage-potato foliage (OSPF) (70:30) containing four levels (0, 25, 50, 75 g of Saccharomyces cerevisiae yeast/kg of fresh forage) as an additive. A randomized complete block design was employed in a 4 x 8 factorial scheme (levels, times) with three replications to determine the impact of yeast levels and incubation times on the degradation of variables. Three Brown Swiss cattle with ruminal fistula were used. Samples of 5 g were incubated in nylon bags for 4, 8, 12, 24, 48, 72, and 96 hours. Time zero (t0) allowed for estimating the soluble fraction. The degradation parameters of DM, CP, NDF, and acid detergent fiber (ADF) were analyzed using a randomized complete block design with three replications. The potential degradation (PD) of DM, NDF, and ADF in silages was not influenced by yeast levels, with means of 89.55, 85.22, and 83.45%, respectively. This trend was also observed for effective degradations at 2, 5, and 8%/hour of DM, NDF and ADF. Silages containing 25, 50, and 75 g of yeast/kg of OSPF, which did not differ from each other, showed significant superiority (p<0.05) in CP degradation compared to yeast-free silage. In the latter silage, the indigestible rate (i) of CP was higher than in silages containing yeast, with degradation rates (c) of 2%/hour. Among the silages, the one containing 25 g/kg of OSPF exhibited high potential CP degradation (93.18%), effective at 2%/hour (87.48%), and a low indigestible rate (6.82%), classifying it as a forage resource with good nutritional quality.